Prediksi Diabetes Menggunakan Artificial Neural Network - Wirapati, Satya; Astuti, Luh Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 4 (2023): JELIKU Volume 11 No 4, May 2023DO - 10.24843/JLK.2023.v11.i04.p15, 2023)
Diabetes is one of the non-communicable diseases (NCD) which has now become a serious threat to global health. Quoting from the World Health Organization (WHO) data, 70% of the total deaths in the world are caused by non-communicable diseases. The position of diabetes as one of the silent killers in Indonesia may increase if this disease is not handled properly. In 2016, the percentage of deaths due to diabetes in Indonesia reached 6.7% and was the second highest after Sri Lanka. This figure is quite high because 2 out of 3 diabetics in Indonesia do not know that they have diabetes. Most of them only access health services when they are in a deteriorating condition, and even have complications. This became the basis for our group to create an expert system application using a deep learning/artificial neural network algorithm that aims to predict a patient will have acute diabetes with great accuracy.